PLEOMORPHIC XANTHOASTROCYTOMA ASSOCIATED WITH VONRECKLINGHAUSEN NEUROFIBROMATOSIS - (:unkn) unknown (SPRINGER, 1993)
The authors present a case of pleomorphic xanthoastrocytoma that occurred in a 14-year-old boy with von Recklinghausen's neurofibromatosis. The circumscribed turmor with a cystic component was located in the medial right temporal lobe. The designation of pleomorphic xanthoastrocytoma has been suggested for this neoplasm on the basis of its unique histological features. These include positive glial fibrillary acidic protein staining.
Keywords: PLEOMORPHIC XANTHOASTROCYTOMA; BENIGN GLIOMA; GLIAL FIBRILLARY ACIDIC PROTEIN; VONRECKLINGHAUSEN NEUROFIBROMATOSIS; YOUNG SUBJECTS; GLIOMA